Schooling and Identity: A Qualitative Analysis of Self-Portrait Drawings of Young Indigenous People from Chiapas, Mexico - Esteban-Guitart, Moises; Monreal-Bosch, Pilar; Perera, Santiago; Bastiani, José (Frontiers in Psychology, 2017)
One of the features associated with schooling and formal education is their decontextualized nature, a characteristic that has been related to the advancement of logical abstract thinking. The aim of this study was to compare and contrast self-portraits through the graphical representations and verbal explanations made by young indigenous people from the Altos de Chiapas with different educational levels ranging from primary school to university. Participants were of the same age. The results show the abstract nature (as opposed to the concrete character) of some of the self-portraits made by the group of university students and the prevalence of individual aspects (rather than social contextual factors) especially within this same group.